Investigating Teacher’s Linguistic Competence in Teaching English for Academic Purposes - Bontisesari Wahyoedi; Irma Rasita Gloria Barus (ITScience (Information Technology and Science), 2022)
Being a language teacher means they are not only fluent in using the target language but also possess competence in the study of language. Hence, linguistic knowledge is one essential skill a language teacher needs to possess. Using a descriptive qualitative research design of the content analysis, this article aimed to investigate the linguistic competence of an English teacher and its implementation in the classroom. The recordings of online classroom sessions of an English for Academic Purposes course were observed. The teacher, as the main object of the study, was also interviewed to enrich understanding through open-ended questions. The collected audio-visual data was then analyzed and categorized based on the linguistic features employed by the teacher. While existing studies focus on the linguistic competence of pre-service teachers, the findings are inclined to negative results. Hence, by investigating the teaching practice of a teacher with 30 years of experience, the findings revealed the descriptions of linguistic features evident in the data and explained how those features helped the teacher in carrying out the teaching and learning session. Subsequently, it is recommended that English teachers increase their language awareness as well as linguistic competence so that they can perform better in meeting the students’ needs in acquiring and improving English language skills.